There are many futures for pastoralism in Africa - Cullis, A. (International Livestock Research Institute, 2011)
Adrian Cullis from FAO Ethiopia reflects on the recent conference in Addis Ababa on the future of pastoralism in Africa. The event's fundamental take home message is that "there is a future for pastoralism in Africa." However, it looks like there will be different futures and different forms of pastoralism - with winners and losers. He also outlines the work FAO does in this area, and comments on some issues like gender and productivity issues (of rangelands, of livestock) that received insufficient attention in the meeting. Commenting on the role of ILRI in this area, he suggested areas where partnerships between FAO and ILRI might be feasible. He noted the complementarity between ILRI's strong research focus and FAO's project and policy emphasis. The Addis Ababa conference (21-23 March 2011) was organized by the Future Agricultures Consortium with Tufts University.